2021
DOI: 10.3122/jabfm.2021.04.210039
|View full text |Cite
|
Sign up to set email alerts
|

Provider Impacts of Socioeconomic Risk Screening and Referral Programs: A Scoping Review

Abstract: Background: Initiatives to identify and intervene on patients' socioeconomic needs in the context of health care delivery are expanding. Little information has been compiled across studies on health care providers' knowledge, attitudes, beliefs, and behaviors (KABB) regarding socioeconomic risk screening and referral interventions.Methods: We conducted a systematic scoping review of providers' KABB related to health care-based socioeconomic risk screening and referral interventions using several search engines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 82 publications
1
20
0
Order By: Relevance
“…The identified personal attributes provide important considerations for the educational system responsible for the training of doctors and nurses. Consistent with our findings, Quiñones-Rivera and colleagues drew attention to a lack of provider knowledge to be able to address patients' social needs [19]. Targeted curricula for trainees and continuing professional development programs for qualified doctors and nurses could improve their comfort and confidence to conduct an assessment.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The identified personal attributes provide important considerations for the educational system responsible for the training of doctors and nurses. Consistent with our findings, Quiñones-Rivera and colleagues drew attention to a lack of provider knowledge to be able to address patients' social needs [19]. Targeted curricula for trainees and continuing professional development programs for qualified doctors and nurses could improve their comfort and confidence to conduct an assessment.…”
Section: Discussionsupporting
confidence: 79%
“…Previous studies have focused on the readiness of doctors and nurses to use social needs screening tools [3,[13][14][15][16][17][18][19], primarily screening tools for domestic violence [13-15, 18, 20-25]. A recent systematic review by Quiñones-Rivera and colleagues [19] found that providers held generally positive attitudes and beliefs about the importance of addressing social needs, however, they identified barriers to social needs screening including concerns regarding patient discomfort at being questioned, increasing pressure on time and workflow, risk to patient-provider relationships, and a lack of knowledge about how to address identified social needs [19]. A number of studies focused on the readiness of doctors and nurses in primary healthcare settings [3,17,[26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“… 31 Furthermore, attitudes toward screening can improve following implementation of screening programs. 58 Clinical staff have also expressed reservations about screening, including a belief that screening is beyond their scope of practice, 59 , 60 fear of offending patients, 28 , 55 , 59 , 61 , 62 perceived or real lack of resources to address needs, 55 , 62 , 63 and concern about disclosure increasing risk such as with IPV. 59 In the case of IPV screening, however, evidence shows patient acceptability 23 , 53 , 54 and satisfaction 64 along with a single study finding no risk of violence with disclosure.…”
Section: Resultsmentioning
confidence: 99%
“…One potential explanation for why staff screened patients who visited the clinic more frequently is staff may be more familiar with these patients' needs as a result of these patients' high visit rates. Staff may perceive HRSN screening as challenging, as prior work suggests time constraints, [12][13][14]16,20 insufficient training, 12,14,20 concern about lack of resources to address positive screening results, 13,14,20,26 and recognition that patients are being asked to provide sensitive information that was not previously required all may lead to lower implementation rates of HRSN screening. 12,18,27 In the setting of these challenges, staff may find it easier to pre-select patients with whom staff have a rapport and have a need staff are already familiar with, which may be evidenced by screening patients with high visit rates.…”
Section: Discussionmentioning
confidence: 99%
“…1011 FQHCs must therefore understand how to effectively implement HRSN screening to improve reach of HRSN screening and ensure sufficient data collection, development of appropriate referral programs, and partnerships with local community organizations. Despite the importance of screening for HRSN for their patients, FQHCs and CHCs face challenges to performing universal HRSN screening due to limited resources [12][13][14] and lack of standardized screening implementation strategies. 6,15 To our knowledge, there is a dearth of peer-reviewed literature that examines implementation approaches for HRSN screening [15][16][17] in resource-constrained settings.…”
Section: Introductionmentioning
confidence: 99%